Exploring the Attractiveness of @Mursid241 Content on TikTok Media Sosial - Denta Yuvi Rezkyanda; Lisa Mardiana (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
Content appeal is an approach to understanding why and how certain content attracts an audience. With the increasing popularity of TikTok, various types of content have emerged, including entertaining content. This research aims to understand the factors that make Mursids' content attractive to TikTok users. The research method used is a qualitative method that uses a descriptive approach, as well as a survey of TikTok users who often consume the content. The results showed that the attractiveness of Mursid content on TikTok is influenced by several factors, namely the type of content, visual characteristics, unique narrative characteristics, relevance and active engagement of content creators with their audience, emotion and empathy, interaction and response between content creators and audience, and ongoing trends and context. This research provides insights for creators of entertaining daily activities on effective strategies to increase the appeal and reach of their content on the TikTok platform.